Alimentación de cerdos en crecimiento y engorde con raciones ricas en heno de alfalfa - Esteves, R.; Cervellini, J. E. (Semiárida, 2020)
Alimentación de cerdos en crecimiento y engorde con raciones ricas en heno de alfalfa